Genetic diversity of horseshoe crabs (Carcinoscorpius rotundicauda and Tachypleus gigas) in Demak, Madura and Balikpapan waters based on Random Amplified Polymorphic DNA marker - AINI, NAILA KHURIL; MASHAR, ALI; MADDUPPA, Hawis H.; WARDIATNO, YUSLI (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2020)
Horseshoe crab is an exotic and protected marine organism in Indonesia and is considered as the living fossil animal in the world. IUCN conservation status of Carcinoscorpius rotundicauda and Tachypleus gigas is still Data Deficient, and in Indonesia research on genetic population is lacking, if any. This study aims to reveal genetic diversity of C. rotundicauda and T. gigas populations in northern Java (Demak and Madura) and Balikpapan waters. This research was conducted by using molecular analysis with genetic markers Random Amplified Polymorphic DNA (RAPD). The primers used in this study were OPB 06, OPG 10, and OPX 03. The results showed that the highest polymorphism of C. rotundicauda was found in Demak (74.6667%) and heterozygosity was 0.2669. Furthermore, T. gigas had the highest polymorphism in Madura (74.3590%) and heterozygosity was 0.25551. Based on pairwise comparison tests, populations of C. rotundicauda and T. gigas in Demak, Madura, and Balikpapan were significantly different (p